The effect of low-volume high-intensity interval training on body composition and cardiorespiratory fitness: A systematic review and meta-analysis - Sultana, R. N.; Sabag, A.; Keating, S. E.; Johnson, N. A. (Sports Medicine, 2019)
Background: Evidence for the efficacy of low-volume high-intensity interval training (HIIT) for the modulation of body composition is unclear. Objectives: We examined the effect of low-volume HIIT versus a non-exercising control and moderate-intensity continuous training (MICT) on body composition and cardiorespiratory fitness in normal weight, overweight and obese adults. We evaluated the impact of low-volume HIIT (HIIT interventions where the total amount of exercise performed during training was = 500 metabolic equivalent minutes per week [MET-min/week]) compared to a non-exercising control and MICT. Methods: A database search was conducted in PubMed (MEDLINE), EMBASE, CINAHL, Web of Science, SPORTDiscus and Scopus from the earliest record to June 2019 for studies (randomised controlled trials and non-randomised controlled trials) with exercise training interventions with a minimum 4-week duration. Meta-analyses were conducted for between-group (low-volume HIIT vs. non-exercising control and low-volume HIIT vs. MICT) comparisons for change in total body fat mass (kg), body fat percentage (%), lean body mass (kg) and cardiorespiratory fitness. Results: From 11,485 relevant records, 47 studies were included. No difference was found between low-volume HIIT and a non-exercising control on total body fat mass (kg) (effect size [ES]: - 0.129, 95% confidence interval [CI] - 0.468 to 0.210; p = 0.455), body fat (%) (ES: - 0.063, 95% CI - 0.383 to 0.257; p = 0.700) and lean body mass (kg) (ES: 0.050, 95% CI - 0.250 to 0.351; p = 0.744), or between low-volume HIIT and MICT on total body fat mass (kg) (ES: - 0.021, 95% CI - 0.272 to 0.231; p = 0.872), body fat (%) (ES: 0.005, 95% CI - 0.294 to 0.304; p = 0.974) and lean body mass (kg) (ES: 0.030, 95% CI - 0.167 to 0.266; p = 0.768). However, low-volume HIIT significantly improved cardiorespiratory fitness compared with a non-exercising control (p < 0.001) and MICT (p = 0.017). Conclusion: These data suggest that low-volume HIIT is inefficient for the modulation of total body fat mass or total body fat percentage in comparison with a non-exercise control and MICT. A novel finding of our meta-analysis was that there appears to be no significant effect of low-volume HIIT on lean body mass when compared with a non-exercising control, and while most studies tended to favour improvement in lean body mass with low-volume HIIT versus MICT, this was not significant. However, despite its lower training volume, low-volume HIIT induces greater improvements in cardiorespiratory fitness than a non-exercising control and MICT in normal weight, overweight and obese adults. Low-volume HIIT, therefore, appears to be a time-efficient treatment for increasing fitness, but not for the improvement of body composition.